My Mate Food & Friends Promotion Strategy with Integrated Marketing Communication to have Awareness in Bintaro Jaya - Widyaraahman, Aditya; Hudrasyah, Herry (Journal of Business and Management, 2013)
My Mate Food & Friends’ is real culinary businesses in Bintaro Jaya, before My Mate Food & Friends stand; there was named Moe Café, Family and Restaurant. Therefore Moe Café changed into My Mate Food & Friends to follow the market growth as the writer also directly involve in running this real culinary business. The writer used Integrated Marketing Communication model strategy business. In this research the writer used exploratory research method. The results explorative research is going to be used field observation, interview with key performance, and questionnaire variables. The problem that rose in this research is about promotion strategy that performs by My Mate Food & Friends management to have costumer awareness for My Mate Food & Friends, and finding solution that management should do to become new concept culinary business in concept that accepted, also competitive with other competitors. Therefore, based on the analysis, the writer giving conclusion and recommendation for My Mate Food & Friends management they should do. The reason of this paper is to build new culinary business development in Bintaro Jaya. Other wise the tools of IMC need to be integrated. IMC previous studies, to sells the brand with IMC approach, and the scale to evaluated potential target audience, and costumer expectation of brand awareness to sells My Mate Food & Friends brand. Other data is gathered from some interview to three key performances. The impact of this research to the society is gives society a better place to have new experience in culinary life style, introducing people to stay in their area rather to go out from Bintaro Jaya. The society issue is the local organization that sometimes they must be manage to not bother other people business. Keywords-component; Integrated Marketing Communication, Potential Target audience,Promotion Strategy, Mix Marketing. Category: Marketing